HTLV-1 drives vigorous clonal expansion of infected CD8(+) T cells in natural infection - Melamed, Anat (Retrovirology, 2015)
BACKGROUND: Human T-lymphotropic Virus Type I (HTLV-1) is a retrovirus that persistently infects 5–10 million individuals worldwide and causes disabling or fatal inflammatory and malignant diseases. The majority of the HTLV-1 proviral load is found in CD4(+) T cells, and the phenotype of adult T cell leukemia (ATL) is typically CD4(+). HTLV-1 also infects CD8(+) cells in vivo, but the relative abundance and clonal composition of the two infected subpopulations have not been studied. We used a high-throughput DNA sequencing protocol to map and quantify HTLV-1 proviral integration sites in separated populations of CD4(+) cells, CD8(+) cells and unsorted peripheral blood mononuclear cells from 12 HTLV-1-infected individuals. RESULTS: We show that the infected CD8(+) cells constitute a median of 5 % of the HTLV-1 proviral load. However, HTLV-1-infected CD8(+) clones undergo much greater oligoclonal proliferation than the infected CD4(+) clones in infected individuals, regardless of disease manifestation. The CD8(+) clones are over-represented among the most abundant clones in the blood and are redetected even after several years. CONCLUSIONS: We conclude that although they make up only 5 % of the proviral load, the HTLV-1-infected CD8(+) T-cells make a major impact on the clonal composition of HTLV-1-infected cells in the blood. The greater degree of oligoclonal expansion observed in the infected CD8(+) T cells, contrasts with the CD4(+) phenotype of ATL; cases of CD8(+) adult T-cell leukaemia/lymphoma are rare. This work is consistent with growing evidence that oligoclonal expansion of HTLV-1-infected cells is not sufficient for malignant transformation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12977-015-0221-1) contains supplementary material, which is available to authorized users.